ANALISIS HUKUM TERHADAP KEBIJAKAN KEPESERTAAN TABUNGAN PERUMAHAN RAKYAT BAGI PEKERJA DI INDONESIA - Aristiawan, I Gusti Ngurah (Universitas Mahendradatta, 2024)
People's Housing Savings (Tapera) is one way to give money for housing for low-income people. Approval of the regulations enforcement of the Tapera Act regulated by Government Regulation No. 21 Year 2024 (PP 21/2024) on changes to Government Regulations No. 5 Year 2020 (PP 5/2020) on People's Housing Savings (Tapera) since 20 May 2024 caused conflict from the public, especially workers and employers. The problem raised is the analysis of the policies of participation of people's housing savings for workers in Indonesia. This research is normative using primary, secondary, or tertiary legal sources as data or information sources. With the reduction of wages and wages of the workers by 3 per cent, with the distribution of 0.5 per cent to be borne by the employer and 2.5 per cent by the worker, it has not been possible to realize the trust of NRI UUD 1945 in Article 28H.